Holocene Vegetation and Plant Diversity Changes in the North-Eastern Siberian Treeline Region From Pollen and Sedimentary Ancient DNA - Liu, Sisi; Stoof-Leichsenring, Kathleen R.; Kruse, Stefan; Pestryakova, Luidmila A.; Herzschuh, Ulrike (Frontiers in Ecology and Evolution, 2020)
Although sedimentary ancient DNA (sedaDNA) has been increasingly used to study palaeoecological dynamics, the approach has rarely been compared with the traditional method of pollen analysis for investigating past changes in the vegetation composition and diversity in Arctic treeline areas. Here, we provide a history of floristic composition based on a comparison of sedaDNA and pollen data archived in three Siberian lake sediment cores covering the mid Holocene (7.6–0 cal ka BP), from northern tundra to southern forest in the Omoloy region. Our results show that the sedaDNA approach identifies more plant taxa found in the local vegetation communities, while the corresponding pollen analysis mainly captures the regional vegetation development and has limited ability to reconstruct plant diversity. Across all sites, pollen data reveal the open landscape and climate deterioration from the mid Holocene to late Holocene, with the changes starting first at the tundra site. SedaDNA archives provide a complementary record of the vegetation transition within each lake’s catchment and a distinct latitudinal vegetation type range from larch tree/alder shrub (open larch forest site) to dwarf shrub-steppe (forest tundra) to wet sedge tundra (tundra site). Highest species richness and diversity are found in the mid Holocene (before 4.4 ka) at the tundra site with a diverse range of vegetational habitats, while lowest species richness is recorded for the forest tundra where dwarf willow habitats dominated the lake’s catchment. During the late Holocene, strong declines in species richness and diversity are found at the tundra site with the vegetation changing to a relatively simple community. Nevertheless, plant species richness is mostly higher than at the forest tundra site, which shows a slightly decreasing trend. Plant species richness at the open larch forest site fluctuated through time and is higher than the other sites since around 2.5 ka. Additionally, a weak correlation between the principal component analysis (PCA) site scores of sedaDNA and species richness suggests that climate may not be a direct driver of species turnover within the lake’s catchment. Our data suggest that sedaDNA and pollen have different but complementary abilities for reconstructing past vegetation and species diversity.